RELATIONSHIP BETWEEN FACTORS AND ADOPTION RATE OF CATTLE DEVELOPMENT INNOVATION IN KUANTAN SINGINGI DISTRICT - Haris Susanto; Meli Sasmi; Eldipama Kesambamula; Angga Pramana; Dihan Kurnia (Faculty of Animal and Agricultural Science, Diponegoro University, 2022)
Kuantan Singingi Regency is one of the districts with the potential for oil palm plantations to be integrated with livestock. Innovation in using by-products from plantations and palm oil processing as animal feed and animal manure as fertilizer can be maximally applied using cheap by-product management technology. It can improve the quality and quantity of these by-products. Through the utilization of plantation by-products and palm oil processing as feed, it is predicted to be able to provide support for increasing the cattle population. This study aims to see the relationship between the factors that influence the level of adoption of innovation integration between cattle and oil palm in Kuantan Singing. The results of the study indicate that there is no significant relationship between the characteristics of innovation, breeder characteristics and the performance of the extension worker on the technological innovation of the livestock-palm integration system. With the integration of livestock and palm oil, cattle feed from processed palm oil is beneficial, and cow dung is used as fertilizer for the oil palm plant. With the palm oil program, it is hoped that it can help improve the welfare of oil palm planters and cattle breeders and improve the quality of products produced by palm oil livestock. Breeders still need regular assistance from agricultural extension workers and related agencies regarding applying components of livestock-palm integration technology.